The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1553-2712.1995.tb03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐associated Chest Pain: One‐year Follow‐up

Abstract: Objective: To determine the one-year mortality and incidence of myocardial infarction (MI) post-hospital discharge or ED release for patients with cocaine-associated chest pain.Methods: A prospective, observational study of an inception cohort of consecutive patients who presented to one of four municipal hospital EDs with cocaine-associated chest pain. Patients were followed for one year from the end of the enrollment period. Main outcome parameters were the one-year actuarial survival and the frequency of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…In another cohort of 203 patients with cocaine-associated chest pain followed up for 1 year, 60% reported continued cocaine use. 39 Although no MI or death occurred among those claiming abstinence, 2 nonfatal MIs and 6 deaths occurred in patients with persistent cocaine use (although none were attributed to MI). Weber et al 49 reported a 1.6% rate of nonfatal MI during a 30-day follow-up of patients who presented with cocaine-associated chest pain and in whom MI was excluded.…”
Section: Complications and Prognosismentioning
confidence: 99%
See 3 more Smart Citations
“…In another cohort of 203 patients with cocaine-associated chest pain followed up for 1 year, 60% reported continued cocaine use. 39 Although no MI or death occurred among those claiming abstinence, 2 nonfatal MIs and 6 deaths occurred in patients with persistent cocaine use (although none were attributed to MI). Weber et al 49 reported a 1.6% rate of nonfatal MI during a 30-day follow-up of patients who presented with cocaine-associated chest pain and in whom MI was excluded.…”
Section: Complications and Prognosismentioning
confidence: 99%
“…Recurrent chest pain is less common and MI and death are rare among patients who discontinue cocaine. 39,49 No established drug treatments exist for cocaine dependency, however, and recidivism is high among patients with cocaine-associated chest pain (60% admit to cocaine use in the next year). 39 Several options for psychosocial intervention exist, including individual and group counseling, psychotherapy, and cognitive therapy.…”
Section: Discharge Management and Secondary Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnosis of cocaine-related chest pain is broad and includes acute coronary syndrome (ACS), aortic dissection, pneumothorax, pneumomediastinum, pneumopericardium, and pulmonary infarction [3][4][5][6][7][8]. Diagnostic and treatment strategies are similar to that of other ED patients with chest pain.…”
Section: Introductionmentioning
confidence: 99%